The impact of financial analysis on investment decisions in banks (A field study on the branches of banks operating in the northern state – Dongola) - AwadAllah, Derar AbdelMukrim Hassan; Al-Amin, Muawiya Yahya Haj (Journal of Economic, Administrative and Legal Sciences, 2022)
The problem with research on the impact of the use of credit analysis on the decision to invest in banks and to identify deficiencies that lead to the emergence of the problem of debt and defaulted credit facilities. The most important objectives of the study illustrate the possibility of relying on financial hub in the process of decision Atkhaz. Researcher used the Alastbaty and inductive, historical and descriptive analytical approach. The study was able to verify the validity of the hypotheses and draw a number of results, which are summarized as follows: The management of banks, Northern State- Dongola based on the audited financial statements after the attached report of the auditor’s decision to grant credit. The study concluded by a number of recommendations including: is essential for the management of banks, Northern State- Dongola increasing concern for the claim were made by the financial position of the establishments that apply for credit.